Violence tendency, resilience and decision-making in football referees of various classes. A study in Turkey - SELVİ, SABİT and KARAGÜN, ELİF (Progress in Nutrition, 2021)
The objective is to investigate; violence tendency, resilience and decision-making styles of Turkey football referees and to find out whether these characteristics change with respect to age, gender, marital status, education, economic status, refereeing years-class, and exposure to violence. This study was conducted with 1115 football referees of various classes who were selected using the cluster sampling method. When the data were analysed with the SPSS 18.0 package program, the level of resilience was found higher in women, married, older individuals, those with higher education-income level and those who were exposed to violence. The violence tendency scores were found significant in favour of men and those exposed to violence, the 18-23 age interval, those aged over 36, those received associate degree education and those with a low income and an income in the range of 2501-3000. With respect to decision-making styles, the rational decision-making score was found significant in favour of those married and with high economic income, the intuitive decision-making score in favour of those who have a PhD and high level of income and the dependent and avoidant decision-making score in favour of those who have a PhD and men. The spontaneous decision-making was found significant in favour of men, singles, younger referees and in those with a PhD level of education.